Lived experiences of frontline healthcare providers offering maternal and newborn services amidst the novel corona virus disease 19 pandemic in Uganda: A qualitative study - Kayiga, Herbert; Genevive, Diane A.; Amuge, Pauline M.; Ssemata, Andrew S.; Nanzira, Racheal S.; Nakimuli, Annettee (PLoS One, 2021)
The COVID-19 pandemic has brought many health systems in low resource settings to their knees. The pandemic has had crippling effects on the already strained health systems in provision of maternal and newborn healthcare. With the travel restrictions, social distancing associated with the containment of theCOVID-19 pandemic, healthcare providers could be faced with challenges of accessing their work stations, and risked burnout as they offered maternal and newborn services. This study sought to understand the experiences and perceptions of healthcare providers at the frontline during the first phase of the lockdown as they offered maternal and newborn health care services in both public and private health facilities in Uganda with the aim of streamlining patient care in face of the current COVID-19 pandemic and in future disasters. Methods Between June 2020 and December 2020, 25 in-depth interviews were conducted among healthcare providers of different cadres in eight Public, Private-Not-for Profit and Private Health facilities in Kampala, Uganda. The interview guide primarily explored the lived experiences of healthcare providers as they offered maternal and newborn healthcare services during the COVID-19 pandemic. All of the in depth interviews were audio recorded and transcribed verbatim. Themes and subthemes were identified using both inductive thematic and phenomenological approaches. Results The content analysis of the in depth interviews revealed that the facilitators of maternal and newborn care service delivery among the healthcare providers during the COVID-19pandemic included; salary bonuses, the passion to serve their patients, availability of accommodation during the pandemic, transportation to and from the health facilities by the health facilities, teamwork, fear of losing their jobs and fear of litigation if something went wrong with the mothers or their babies. The barriers to their service delivery included; lack of transport means to access their work stations, fear of contracting COVID-19 and transmitting it to their family members, salary cuts, loss of jobs especially in the private health facilities, closure of the non-essential services to combat high patient numbers, inadequate supply of Personal Protective equipment (PPE), being put in isolation or quarantine for two weeks which meant no earning, brutality from the security personnel during curfew hours and burnout from long hours of work and high patient turnovers. Conclusion The COVID-19 Pandemic has led to a decline in quality of maternal and newborn service delivery by the healthcare providers as evidenced by shorter consultation time and failure to keep appointments to attend to patients. Challenges with transport, fears of losing jobs and fear of contracting COVID-19 with the limited access to personal protective equipment affected majority of the participants. The healthcare providers in Uganda despite the limitations imposed by the COVID-19 pandemic are driven by the inherent passion to serve their patients. Availability of accommodation and transport at the health facilities, provision of PPE, bonuses and inter professional teamwork are critical motivators that needed to be tapped to drive teams during the current and future pandemics.